Social cohesion and immigration in Europe and North America mechanisms, conditions, and causality - Koopmans, Ruud 1961-; Lancee, Bram; Schaeffer, Merlin (Routledge advances in sociology, 2015)
"Concerns about immigration and the rising visibility of minorities have triggered a lively scholarly debate on the consequences of ethnic diversity for trust, cooperation, and other aspects of social cohesion. In this accessibly written volume, leading scholars explore where, when, and why ethnic diversity affects social cohesion by way of analyses covering the major European immigration countries, as well as the United Sates and Canada. They explore the merits of competing theoretical accounts and give rare insights into the underlying mechanisms through which diversity affects social cohesion. The volume offers a nuanced picture of the topic by explicitly exploring the conditions under which ethnic diversity affects the 'glue' that holds societies together. With its interdisciplinary perspective and contributions by sociologists, political scientists, social psychologists, as well as economists, the book offers the most comprehensive analysis of the link between ethnic diversity and social cohesion that is currently available"--